Immuno−oncological effects of aerobic exercise combined with anti−PD−L1 antibody blockade in a murine breast cancer model - Hekmatikar, Amirhossein Ahmadi; Agha-Alinejad, Hamid; Yousefi-Ahmadipour, Aliakbar; Shamsi, Mahdieh Molanouri; Daud, D. Maryama Awang (Frontiers in Oncology, 2026)
Immunotherapy has emerged as a crucial approach in cancer treatment, particularly through targeting immune checkpoints such as programmed cell death protein 1 (PD−1) and its ligand programmed cell death 1 ligand 1 (PD−L1). Blocking antibodies against PD−1/PD−L1 have demonstrated the potential to activate tumor−specific immune cells, particularly CD4+ and CD8+ T cells. Recently, research in exercise oncology has underscored the role of physical activity in augmenting immune function in cancer settings. This study explored the combined impact of aerobic exercise and anti−PD−L1 antibody administration on immunological and physiological responses in a murine breast cancer model. Materials and Methods: Thirty female BALB/c mice were divided into five experimental groups: Patient control group (n=6), Exercise+induction+ control (n=6), Exercise+induction+exercise (n=6), Exercise+induction+anti-PD-L1 (n=6), and Exercise induction exercise + anti-PD−L1 (n=6). After a treadmill acclimation period, mice underwent two 6-week initial training protocols, followed by an additional 4-week protocol post-tumor induction. Following tumor induction, the PD−L1anti−PD−L1 antibody was administered. One-way analysis of variance (ANOVA) was applied to evaluate experimental variables. Results: Statistical analyses showed that, relative to the PCG, mice receiving the combined intervention of EIE and EIE + A displayed higher intratumoral CD4+ and CD8+ T cell densities and smaller final tumor volumes. Similar but less pronounced trends were observed in the EIE and EIE+A. Conclusion: Within the limits of the current design, the combination of aerobic exercise with PD−L1 immune checkpoint blockade was associated with increased tumor−infiltrating CD4+ and CD8+ T−cell density and reduced tumor burden. These findings suggest a potential interaction that warrants evaluation in future studies incorporating a PD−L1−monotherapy group to clarify independent and combined effects.